Visual-Based Communication Training: Reducing Pediatric Induced Practitioner Stress and Enhancing Clinical Ergonomics - Ade Elza Buana; Desi Andriyani (Inovasi Analisis Data, 2025)
Objective: Drawing on psychology and cognitive theories, the current study explores visual-based communication training in order to alleviate stress among practitioners provoked by pediatric clinical experiences, and to improve clinical ergonomics. Methods: The research adopted a quantitative, theory-based design using a structured survey and variance-based structural equation modelling to explore the links between visual communication characteristics, practitioner self-efficacy and work-related stress. The project was nested in Cognitive Load Theory, Social Cognitive Theory and the Transactional model of stress and coping to describe how ergonomic communication tools influence practitioner outcomes. Findings: Results indicate that visual language doesn’t significantly reduce the level of work- related stress; but on the other hand, it has an indirect effect which improves practitioners’ self-efficacy. Communication interactivity and narrative depth, closely related to the practitioners' perceived ability of successfully handling pediatric clinical demands are a key factor in stress reduction. Self-efficacy is the major psychological process by which ergonomic communication design leads to well-being at work. Novelty: This research contributes to the ergonomics and occupational health literature by combining visual communication theory with psychological self-regulation mechanisms, while promoting ‘self-efficacy’ as a proximal mediator as opposed to considering the tools of communication as direct interventions on stress modification. Research Implications: These results provide direction for the development of practitioner-focused communication training and ergonomic interventions to enhance occupational well-being and sustained clinical performance.